Blood-brain barrier dysfunction and cerebral small vessel disease (arteriolosclerosis) in brains of older people. - Bridges, L; Andoh, J; Lawrence, A; Khoong, C; Poon, W; Esiri, M; Markus, H; Hainsworth, A (Lippincott Williams and Wilkins, 2014)
The blood-brain barrier protects brain tissue from potentially harmful plasma components. Small vessel disease (SVD; also termed arteriolosclerosis) is common in the brains of older people and is associated with lacunar infarcts, leukoaraiosis, and vascular dementia. To determine whether plasma extravasation is associated with SVD, we immunolabeled the plasma proteins fibrinogen and immunoglobulin G, which are assumed to reflect blood-brain barrier dysfunction, in deep gray matter (DGM; anterior caudate-putamen) and deep subcortical white matter (DWM) in the brains of a well-characterized cohort of donated brains with minimal Alzheimer disease pathology (Braak Stages 0-II) (n = 84; aged 65 years or older). Morphometric measures of fibrinogen labeling were compared between people with neuropathologically defined SVD and aged control subjects. Parenchymal cellular labeling with fibrinogen and immunoglobulin G was detectable in DGM and DWM in many subjects (>70%). Quantitative measures of fibrinogen were not associated with SVD in DGM or DWM; SVD severity was correlated between DGM and DWM (p < 0.0001). Fibrinogen in DGM showed a modest association with a history of hypertension; DWM fibrinogen was associated with dementia and cerebral amyloid angiopathy (all p < 0.05). In DWM, SVD was associated with leukoaraiosis identified in life (p < 0.05), but fibrinogen was not. Our data suggest that, in aged brains, plasma extravasation and hence local blood-brain barrier dysfunction are common but do not support an association with SVD.